2012
DOI: 10.1128/mbio.00045-12
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian-Transmissible H5N1 Influenza: Facts and Perspective

Abstract: Two recently submitted (but as yet unpublished) studies describe success in creating mutant isolates of H5N1 influenza A virus that can be transmitted via the respiratory route between ferrets; concern has been raised regarding human-to-human transmissibility of these or similar laboratory-generated influenza viruses. Furthermore, the potential release of methods used in these studies has engendered a great deal of controversy around publishing potential dual-use data and also has served as a catalyst for deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…Although available evidence supports the fact that asymptomatic infections with H5N1 can occur in persons exposed to the virus, the evidence does not suggest that asymptomatic infections are common or that the case-fatality rate for H5N1 has been significantly overestimated (5). There is no evidence to support the statement by Palese and Wang that "the case-fatality rate that is offered by the WHO-and that is driving this controversy-is likely orders of magnitude too high" (1).…”
contrasting
confidence: 48%
“…Although available evidence supports the fact that asymptomatic infections with H5N1 can occur in persons exposed to the virus, the evidence does not suggest that asymptomatic infections are common or that the case-fatality rate for H5N1 has been significantly overestimated (5). There is no evidence to support the statement by Palese and Wang that "the case-fatality rate that is offered by the WHO-and that is driving this controversy-is likely orders of magnitude too high" (1).…”
contrasting
confidence: 48%
“…30,31 Both concluded that, if the 4 Hong Kong Clade 0 studies were excluded and if the 13 studies that conform to official WHO criteria are analyzed, the seropositivity rate is approximately 0.5%. A total of 26 out of 5,487 people were seropositive for H5N1 in those studies.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 99%
“…41-45 Indeed, some have argued that the 1997 HK outbreak is irrelevant due to the genetic dissimilarity of the 1997 strain from later H5N1 strains. It is possible, as was suggested in a recent review, 46 that strains of different genotypes may differ in infectivity and transmissibility characteristics.…”
Section: Implications Of Our Hypothesismentioning
confidence: 99%